Impact of Emergency Remote Teaching on Student Anxiety: - Conrad S. Zygmont; Charlene R. Reinecke; Daniel R. du Plooy (Pan-African Journal of Education and Social Sciences)
The COVID-19 pandemic caused pandemonium in the education, finance, and health sectors worldwide. The education sector had to respond quickly by moving teaching and learning activities generally designed for face-to-face to online delivery. These rapid changes and the negative impacts that accompanied them brought about an increase in anxiety for many students. Using a mixed-methods approach, this study described students’ perceptions of emergency remote teaching (ERT) at a private Seventh-day Adventist higher education institution in Southern Africa and the relationship between their ERT experience and general anxiety levels. We also examined the mediating roles of COVID-related knowledge, conspiracy beliefs, perceived risk, and levels of religiosity/spirituality in this relationship. The results suggest that students experienced both positive and negative impacts of ERT, but negative ERT experiences were strongly associated with increased student anxiety. Within the study sample, perceived COVID-19 risk, and religiosity/spirituality partially mediated the effect of ERT on student anxiety, whereas conspiracy beliefs and COVID-19 knowledge did not. This study highlights faculty's role in reducing student anxiety through a holistic approach that addresses scholastic, social, psychological, and spiritual domains.